2000
DOI: 10.1016/s0005-2736(00)00133-4
|View full text |Cite
|
Sign up to set email alerts
|

Emerging mechanisms for heavy metal transport in plants

Abstract: Heavy metal ions such as Cu(2+), Zn(2+), Mn(2+), Fe(2+), Ni(2+) and Co(2+) are essential micronutrients for plant metabolism but when present in excess, these, and non-essential metals such as Cd(2+), Hg(2+) and Pb(2+), can become extremely toxic. Thus mechanisms must exist to satisfy the requirements of cellular metabolism but also to protect cells from toxic effects. The mechanisms deployed in the acquisition of essential heavy metal micronutrients have not been clearly defined although a number of genes hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
321
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 536 publications
(327 citation statements)
references
References 98 publications
1
321
0
5
Order By: Relevance
“…It has previously been suggested that the Cys dipeptides and His-rich domains in heavy metal ATPases may be involved in heavy metal-binding (Solioz and Vulpe, 1996;Williams et al, 2000), and the findings presented here confirm these speculations for the TcHMA4 protein. Based on the association constants for the binding of heavy metals to di-Cys and di-His residues (Motekaitis et al, 1997), the His and Cys repeats, particularly in the longer peptide, should provide a large number of high-affinity binding sites for a range of heavy metals and micronutrients, including Cd, Pb, mercury, Zn, Co, Ni, and Cu.…”
Section: Possible Function Of Tchma4 In Heavy Metal Hyperaccumulationsupporting
confidence: 88%
“…It has previously been suggested that the Cys dipeptides and His-rich domains in heavy metal ATPases may be involved in heavy metal-binding (Solioz and Vulpe, 1996;Williams et al, 2000), and the findings presented here confirm these speculations for the TcHMA4 protein. Based on the association constants for the binding of heavy metals to di-Cys and di-His residues (Motekaitis et al, 1997), the His and Cys repeats, particularly in the longer peptide, should provide a large number of high-affinity binding sites for a range of heavy metals and micronutrients, including Cd, Pb, mercury, Zn, Co, Ni, and Cu.…”
Section: Possible Function Of Tchma4 In Heavy Metal Hyperaccumulationsupporting
confidence: 88%
“…Cd uptake and efflux, and the inhibition of metal transport by Cd, are well characterized in plants, yeast, and mollusk (6,8,(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). In mammalian-cultured cells, many studies of Cd transport and inhibition of divalent cation transport by Cd have shown Cd uptake and toxicity (11,42,43,(60)(61), but there were no studies correlating Cd uptake with toxicity in any organ or specific cell type of any intact vertebrate.…”
Section: Discussionmentioning
confidence: 99%
“…The subcellular events by which Cd is taken up by cells or removed from cells remain obscure, although such knowledge could provide potential therapeutic targets for protection or intervention against Cd toxicity. Several proteins transport Cd into bacteria, yeast, plants, and mammalian cells in culture (6)(7)(8)(9)(10)(11), but their specific roles in causing toxicity are unclear; these studies underscore the difficulties in extrapolating from observations in cell culture to the intact animal.…”
mentioning
confidence: 99%
“…In the last decade, the identification of numerous CPx-ATPases and in particular the two human isoforms has brought much attention to these heavy metal transport ATPases (11)(12)(13). These enzymes present interesting structural features such as the N-MBDs repeats in their cytoplasmic amino terminus or the distinct location of the large cytoplasmic loop in relation to their eight TMs.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, ATPases in the PIB subfamily transport transition metals (Cu ϩ , Ag ϩ , Zn 2ϩ , Cd 2ϩ , Pb 2ϩ , and Co 2ϩ ). In light of their substrates, these enzymes appear as central elements in the processes of metal biotolerance and bioaccumulation (11)(12)(13). For instance, the two PIB-type ATPases present in humans are Cu ϩ transporters, and mutations in these proteins are responsible for Menkes' and Wilson's disease (13)(14)(15)(16).…”
Section: P-type Atpases Transport a Variety Of Ions (Hmentioning
confidence: 99%